PARENTS’ KNOWLEDGE OF COMPLEMENTARY FEEDING AND ITS RELATIONSHIP WITH STUNTING: A SURVEY OF PARENTS HAVING CHILDREN IN NURSERIES IN KUANTAN, PAHANG - Norman, Muhamad Fitri; Khattak, Muhammad Muzaffar Ali Khan (International Journal of Allied Health Sciences, 2022)
Introduction: The present study was designed to assess the knowledge of complementary feeding practices among parents who send children to nurseries in Kuantan, Pahang. Method: This research was a cross-sectional survey conducted on 137 parents. A convenient sampling method was used to choose ten selected nurseries in Kuantan, Pahang. A research questionnaire was modified from existing questionnaires and pre-tested. The demographic information and data on feeding practices on stunting were gathered using a questionnaire and the collected data was statistically analysed using SPSS software (version 16.0). The data results were regarded as significant at a probability level of 95% confidence interval (CI, P<0.05). Result: The age range of parents was 31 - 39 years old. The participants either worked in government or private sectors and had a tertiary level of education with on average four members in a family. This survey involved 66 boys (48.2%) and 71 girls (51.8%). The analysis showed that most parents (98.5%) chose 6-12 months as the suitable child’s age to introduce complementary feeding while only two respondents (1.5%) chose 4-5 months. The responses from the parents’ knowledge on the complementary feeding showed that out of 137 children, 78 (56.9%) were normal while 59 children (43.1%) were stunted. Among the 78 normal children, 50:50% were boys and girls. Among the stunted children, 32 (54.2%) of them were girls whilst 27 (45.8%) were boys. There was no association between parents’ knowledge on complementary feeding and stunting. Conclusion: This study shows that considerable number of children are stunted in the study area. Furthermore, this study also indicates that there is no relationship between the parents’ knowledge on complementary feeding practices and stunting.